2019
DOI: 10.1155/2019/1358267
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blood-Derived Products on the Chondrogenic and Osteogenic Differentiation Potential of Adipose-Derived Mesenchymal Stem Cells Originated from Three Different Locations

Abstract: Background. Adipose-derived mesenchymal stem cells (AD-MSCs) from fat tissue considered “surgical waste” during joint surgery may provide a potent source for regenerative medicine. Intra-articular, homologous fat tissue (Hoffa’s fat pad, pouch fat) might possess a superior chondrogenic and osteogenic differentiation potential in comparison to extra-articular, nonhomologous fat. Blood products might further enhance this potential. Methods. AD-MSCs were isolated from fat tissue of 3 donors from 3 locations each,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…HAS is being tested as a possible therapeutic of OA with the aim of preventing joint degeneration. Previous studies showed that freshly isolated HAS more significantly induced cell proliferation of mesenchymal stromal cells, chondrocytes and in bone explants than PRP supplementation [ 15 , 16 , 17 , 18 ]. Moreover, Vacz et al demonstrated that in ischemia conditions, freshly isolated HAS significantly increased cell proliferation within bone fragments when compared to PRP [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAS is being tested as a possible therapeutic of OA with the aim of preventing joint degeneration. Previous studies showed that freshly isolated HAS more significantly induced cell proliferation of mesenchymal stromal cells, chondrocytes and in bone explants than PRP supplementation [ 15 , 16 , 17 , 18 ]. Moreover, Vacz et al demonstrated that in ischemia conditions, freshly isolated HAS significantly increased cell proliferation within bone fragments when compared to PRP [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hyperacute serum (HAS) is a cell and fibrin-free solution, obtained after pressing out fibrin clots, which maintains the highly regenerative capacities of PRP. Previous studies of HAS used the freshly isolated formulation, a liquid version, which proved to induce cell proliferation of chondrocytes, bone marrow mesenchymal stem cells, osteoblasts in cell culture and in a bone ischemic model [ 14 , 15 , 16 , 17 , 18 ]. Kardos et al established a more complex biological model consisting of a human explant co-culture of bone, articular cartilage and synovium, which was used to study the effect of HAS under inflammatory conditions showing that HAS reduced inflammation as well as induced cell proliferation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The general opinion is that PRP and PRP derivatives like platelet lysate stimulate proliferation of a variety of cell types. Many studies looked into the effects of PRP on MSCs derived from various sources, [35][36][37][38] where all studies report on increased proliferation when PRP was compared with conventional culture medium. Likewise, studies describing cell types derived from other tissues in the knee also report on increased proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of hypACT to adipose-derived stem cells cultured in 3D pellets together with chondrogenic differentiation medium resulted in obtaining pellets with good tissue quality and enhanced expression of cartilage-related genes. However, our previous studies evaluating hypACT and PRP influence on OA chondrocytes behaviour were limited to monolayer culture experiments which may not adequately mimic the in vivo conditions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%